A Pixel-Encoder Retinal Ganglion Cell with Spatially Offset Excitatory and Inhibitory Receptive Fields - Keith P. Johnson; Lei Zhao; Daniel Kerschensteiner (Cell Reports, 2018)
Summary: The spike trains of retinal ganglion cells (RGCs) are the only source of visual information to the brain. Here, we genetically identify an RGC type in mice that functions as a pixel encoder and increases firing to light increments (PixON-RGC). PixON-RGCs have medium-sized dendritic arbors and non-canonical center-surround receptive fields. From their receptive field center, PixON-RGCs receive only excitatory input, which encodes contrast and spatial information linearly. From their receptive field surround, PixON-RGCs receive only inhibitory input, which is temporally matched to the excitatory center input. As a result, the firing rate of PixON-RGCs linearly encodes local image contrast. Spatially offset (i.e., truly lateral) inhibition of PixON-RGCs arises from spiking GABAergic amacrine cells. The receptive field organization of PixON-RGCs is independent of stimulus wavelength (i.e., achromatic). PixON-RGCs project predominantly to the dorsal lateral geniculate nucleus (dLGN) of the thalamus and likely contribute to visual perception.